Catamenial pneumothorax: Not only VATS diagnosis - Quercia, Rosatea; De Palma, Angela; De Blasi, Francesco; Carleo, Graziana; De Iaco, Giulia; Panza, Teodora; Garofalo, Giuseppe; Simone, Valentina; Costantino, Michele; Marulli, Giuseppe (Frontiers in Surgery, 2023)
Background: Catamenial pneumothorax (CP) is a rare type of spontaneous, recurring pneumothorax occurring in women, from the day before menstruations until 72 hours after their beginning. Conservative treatment is generally associated with recurrence of CP. Video-assisted thoracic surgery (VATS) approach allows not only to obtain diagnosis, but also to guide definitive treatment of causing lesions, such as ectopic endometrial implants or diaphragmatic defects and fenestrations. We report our experience in VATS management of CP, to focus on its role in CP. Materials and Methods: In this retrospective observational study, we collected data from women referred to our center for CP, from January 2019 to April 2022. All patients underwent VATS approach, with muscle-sparing thoracotomy when diaphragmatic fenestrations were detected, to perform selective diaphragmatic plication and/or partial diaphragmatic resection. Results were analyzed in terms of pneumothorax recurrence after surgical treatment. All patients were referred to gynecologists for medical therapy. Results: Eight women (median age 36 years, range: 21-45), all with right side CP, were included; three already had pelvic endometriosis; two had already undergone lung apicectomy at other institutions. VATS allowed to detect diaphragmatic fenestrations in 7 patients (87,5%), apical bullae in 5 (62,5%). Apicectomy was performed in 5 cases (62,5%); selective diaphragmatic plication in 2 (25%) and partial diaphragmatic resection in 5 (62,5%). Chemical pleurodesis with talc was performed in all, to minimize the risk of recurrence. Pathological diagnosis of endometriosis on the resected diaphragm was achieved in 5 patients (62,5%). No recurrence occurred, except for one woman who stopped medical treatment for endometriosis. Conclusions: In the management of patients with CP, VATS should be recommended not only to obtain an explorative diagnosis of ectopic endometrial implants or diaphragmatic fenestrations, but also to allow the most appropriate surgical treatment and obtain pathological specimens for confirmation and definitive diagnosis of thoracic endometriosis. Medical therapy to achieve ovarian rest is mandatory in the post-operative period and should not be discontinued.